2011
DOI: 10.9744/ing.v13i1.18214
|View full text |Cite
|
Sign up to set email alerts
|

The Washback Effect of the English National Examination (ENE) on English Teachers’ Classroom Teaching and Students’ Learning

Abstract: Abstract:Since 2005, Indonesia has administered the National Examination (NE), from which the result is used as a basis to decide the students' exit from secondary schools. As a high stake testing, the NE has caused various washback effects, both positive and negative. Consequently, the existence of the NE has been accompanied by heated debates and controversies. The pros believe that the NE may improve secondary education standards, while the cons argue that the NE will create injustice and unnecessary anxiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…This role raised controversy among education stakeholders, especially concerning the negative effect of the NE, such as preparation drill, students’ cheating, answer key leakage and the security of test items. In this context, Sukyadi and Mardiani (2011) and Furaidah, Saukah, and Widiati (2015) examined the washback effect of the NE on high-achieving and low-achieving schools. They found that low-achieving schools had more negative washback than high-achieving schools.…”
Section: Secondary Educationmentioning
confidence: 99%
“…This role raised controversy among education stakeholders, especially concerning the negative effect of the NE, such as preparation drill, students’ cheating, answer key leakage and the security of test items. In this context, Sukyadi and Mardiani (2011) and Furaidah, Saukah, and Widiati (2015) examined the washback effect of the NE on high-achieving and low-achieving schools. They found that low-achieving schools had more negative washback than high-achieving schools.…”
Section: Secondary Educationmentioning
confidence: 99%
“…The teachers feel they are being under pressured as to prepare the students to achieve the passing grade in the high-stake test. It does not represent the quality improvement of education because it is dishonesty-provoking, the only standard to measure school quality, unfair, and useless (Sukyadi & Mardiani, 2011). In addition, Furaidah (2013) asserts the involvement of all teachers including those who teach at the tenth and eleventh grade in collecting materials for drilling activities to prepare for the NE.…”
Section: B High-stake Test In Indonesiamentioning
confidence: 99%
“…In some previous studies by Sukyadi & Mardiani (2011), Arapah (2013), Furaidah (2013 Ginting (2014), andSaehu (2015), investigation about the impact of the administration both NE and the SE on the teachers' classroom practices were not their main interest. Mostly they focus the investigation on the impact of NE only or SE only.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations